2008
DOI: 10.1111/j.1525-1438.2007.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adjustment of early-stage ovarian cancer survivors

Abstract: The objectives of this study were to describe the quality of life (QOL), consequences of treatment, complementary therapy use, and factors correlating with psychologic state in 58 survivors of early-stage ovarian cancer since little is known about the QOL of early-stage ovarian cancer survivors. Survivors were interviewed using standardized measures to assess physical, psychologic, social, and sexual functioning; impact of cancer on socioeconomic status; and complementary therapy use. Survivors reported good p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
102
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 38 publications
9
102
2
4
Order By: Relevance
“…However, until today, findings of psycho-oncological distress in women with gynaecological cancer are sparse. In line with other studies [10,11,12], Singer and Schwarz [13] report that 78% of women would like to have psycho-oncological support already during their inpatient stay.…”
Section: Introductionsupporting
confidence: 74%
“…However, until today, findings of psycho-oncological distress in women with gynaecological cancer are sparse. In line with other studies [10,11,12], Singer and Schwarz [13] report that 78% of women would like to have psycho-oncological support already during their inpatient stay.…”
Section: Introductionsupporting
confidence: 74%
“…Skalli et al [20] conducted structured psychiatric interviews with longterm testicular cancer survivors and showed that the presence of an anxiety disorder was significantly associated with FCR. Three studies [21][22][23] with ovarian and breast cancer survivors reported that post-traumatic stress disorder (PTSD) symptoms were positively associated with FCR (r=.42 to .71), but the sole study that used multivariate analyses reported that having a PTSD syndrome did not predict a moderate to high level of FCR [23]. Roth et al [24] observed that a general anxiety disorder (GAD) syndrome was significantly associated with FCR in prostate cancer survivors.…”
Section: Introductionmentioning
confidence: 95%
“…The proponents of universal screening note a high prevalence of distress, as well as options for the successful treatment of such distress when detected ( Stafford & Miller, 2014). Cancer patients require emotional support and psychosocial adaptation to soothe their fears and concerns ( Eyigor, 2010), and high levels of psychological distress have been reported by gynecological cancer survivors, even at five years postdiagnosis ( Ashing-Giwa et al, 2009;Hobbs, 2008;Matulonis et al, 2008;Mirabeau-Beale et al, 2009). Thus, it is important to consider the impact that surviving cancer may have on an individual's well-being, to provide better services following the completion of primary medical treatment.…”
mentioning
confidence: 99%